KUALITAS FISIK PAKAN PELLET BERBAHAN AMPAS SAGU DENGAN PENAMBAHAN INDIGOFERA MENGGUNAKAN LEVEL TEPUNG TAPIOKA YANG BERBEDA - Anwar Efendi Harahap; Wieda Nurwidada Haritsah Zain; Ahmad Fauzi; Bakhendri Solfan (Jurnal Nutrisi Ternak Tropis dan Ilmu Pakan, 2022)
This study aims to determine the physical quality of water content, specific gravit, stack angle, pile density, pile compaction density, and collision resistance pellet product with sago pulp utilization and indigofera leaves. This research used CRD Factorial. Factor A consist of 5 treatments  A4 = 40% Sago Pulp (SP) + 60% Indigofera Leaves (IL), A3 = 30% SP + 70% IL, A2 = 20% (SP) + 80% (IL), A1 = 10% (SP) + 90%, (IL),  A0 = 100% (IL) and Factor B consisting of 2 treatments B1 = 5% Tapioca Flour B2 = 10% Tapioca Flour with 3 replications each. The results showed that the interaction between sago pulp feed ingredients with the addition of indigofera leaves used adhesive material at different levels. It was concluded that the combination of sago and indigofera dregs (40% SP + 60% IL) levels can improve the quality of pellets in terms of density, pile angle, and pellet stack density